Paired assistance and poverty alleviation: Experience and evidence from China - Wang, Quanzhong; Tian, Zhongbao; Zhu, Sai (PloS one, 2024)
This paper used the micro panel data from 2016 to 2019 of 2031 registered poor households in B Town, W County, Lu’an City of Anhui Province in China to analyze the diversified patterns and poverty alleviation effect of paired assistance based on the PSM-DID model. The empirical results show that paired assistance provided by social forces can significantly contribute to the poverty alleviation of poor households, promoting the poverty alleviation rate by 7.8%, which can be concluded through sample matching and control of relevant variables. Furthermore, based on the subsample of poor households with social assistance, we found that external social assistance subject to paired assistance can significantly improve the poverty alleviation rate of poor households by 14.26%, mainly hung on their economic base and strength of poverty alleviation.